2011
DOI: 10.2478/s11756-011-0062-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal development of planktonic rotifers in Slapy Reservoir (Czech Republic)

Abstract: The rotifer community of the canyon shaped Slapy Reservoir was studied over four years, from 2000 to 2003. A total of 38 rotifer taxa were identified in the pelagial zone. The dominant species, Keratella cochlearis, K. quadrata, Polyarthra dolichoptera, P. vulgaris, Synchaeta lakowitziana and Pompholyx sulcata, were similar to other reservoirs in the same area. Tychoplanktic species, which are typical for communities of upstream reservoirs, are reduced in the Slapy Reservoir. The seasonal fluctuation of rotife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Although rotifers generally are present at higher abundances than crustacean species in reservoirs and lakes, the ratio found in our system between their abundances is extremely high (average ratio of rotifer:crustacean abundance in Jiřická Pond=126:1) and notably differ from the ratio recorded in other aquatic systems with higher retention times. For example, the average ratio in Slapy Reservoir (Czech Republic) with 57 days of average time retention is 10:1 (Devetter, 2011); in Řimov Reservoir (Czech Republic) with 90 days of average time retention is 5:1 (Seda and Devetter, 2000); in Saidenbach Reservoir (Germany) with 220 days of average time retention is 4:1 (Hülsmann et al, 2012;personal communication ); or in Lake Śniardwy (Poland) with 260 days of average time retention is 2.5:1 (Ejsmont-Karabin and Kufel, personal communication). This difference in the abundances is likely to be related to their longer generation times (Allan, 1976;Herzig, 1984) which involve a slow growth in the water column.…”
Section: Discussionmentioning
confidence: 99%
“…Although rotifers generally are present at higher abundances than crustacean species in reservoirs and lakes, the ratio found in our system between their abundances is extremely high (average ratio of rotifer:crustacean abundance in Jiřická Pond=126:1) and notably differ from the ratio recorded in other aquatic systems with higher retention times. For example, the average ratio in Slapy Reservoir (Czech Republic) with 57 days of average time retention is 10:1 (Devetter, 2011); in Řimov Reservoir (Czech Republic) with 90 days of average time retention is 5:1 (Seda and Devetter, 2000); in Saidenbach Reservoir (Germany) with 220 days of average time retention is 4:1 (Hülsmann et al, 2012;personal communication ); or in Lake Śniardwy (Poland) with 260 days of average time retention is 2.5:1 (Ejsmont-Karabin and Kufel, personal communication). This difference in the abundances is likely to be related to their longer generation times (Allan, 1976;Herzig, 1984) which involve a slow growth in the water column.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study water temperature was significant for rotifer and cladoceran species. The strong influence of this parameter on several rotifer species (e.g., Keratella cochlearis, Hexarthra sp., Trichocerca similis) has been also demonstrated by Devetter (2011) and Chalkia et al (2012a). It has been reported that temperature affects the metabolic rate of cladocerans and their occurrence and distribution, although the quality and quantity of food are also determinants for the density and biomass of these organisms (Abrantes et al 2006).…”
Section: Zooplankton Species Composition and Variabilitymentioning
confidence: 99%
“…In this study, water temperature was significant for the community of rotifers and cladocerans and especially for the larvae of D. blanci. The influence of temperature on several rotifer species has been well demonstrated (Hoffmann, 1977;Devetter, 1998;2011;Akbulut et al, 2008), while Synchaeta sp. has been also correlated with temperature in Trichonis Lake (Doulka & Kehayias, 2008).…”
Section: Influence Of Physicochemical Parametersmentioning
confidence: 96%
“…During the last few years efforts were made to investigate the zooplankton in the lakes of Western Greece along with the abiotic elements of these ecosystems (Kehayias et al, 2004;Doulka & Kehayias, 2008, 2011Doulka, 2010;Chalkia et al, 2012a, b). As part of this effort, through a one-year investigation, this study aims to investigate the zooplankton community as a biological element relevant in the assessment of the ecological status of this aquatic ecosystem, and also to explore relationships between community dynamics and environmental factors.…”
Section: Introductionmentioning
confidence: 99%